Analisis Kuantitatif Resume Medis Pasien Rawat Inap Kasus Bedah di RS Santa Elisabeth Medan Tahun 2023 - Saragih, Pestaria; Ginting, Nasipta; Ayisah Hutabarat, Nur (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
A medical record is a document that includes information about a patient's identity, their treatment program, actions, exams, and services. One of the sheets contained in the medical record is the medical resume sheet. A medical resume is a summary or conclusion detailing the condition, treatment, examination and actions received by the patient. Incompleteness of medical resumes is one of the problems because medical resumes can provide detailed information about what has happened during the patient's hospitalization, which has an impact on the quality of medical records and services provided by the hospital. The purpose of this study was to quantitatively analyze the medical resumes of patients with inpatient surgical cases at Santa Elisabeth Hospital Medan in 2023. The type of research used is quantitative descriptive research. The sampling technique was Simple Random Sampling. The sample in this study was a medical resume sheet for inpatients with surgical cases totaling 95 medical resumes. The instrument used was a checklist sheet. Data analysis using univariate analysis which results in the distribution and percentage of each variable. The results of this study indicate that based on the completeness of the patient identification review is 100%. Based on the completeness of the important report review is 94.73% and the incompleteness of the important report review is 5.27%. Based on the completeness of the authentication review is 100%. Based on the completeness of the recording review is 96.84% and the incompleteness of the documentation review is 3.16%. It is hoped that the hospital, especially the officers who fill out the medical resume sheet, will always maintain and improve the completeness of the patient's medical resume, and improve the discipline of officers in completing medical records by means of good cooperation between nurses and doctors concerned